IMPLEMENTASI NILAI NILAI AKHLAK DALAM INTERAKSI SOSIAL GENERASI Z DI DESA BAGAN DALAM KEC. TANJUNG TIRAM KAB. BATU BARA - Zahira, Arifah (Jurnal Ikhtibar Nusantara, 2026)
The rapid flow of digitalization has transformed the social interaction patterns of Generation Z, including in coastal rural areas such as Bagan Dalam Village, Tanjung Tiram District, Batu Bara Regency. This is characterized by a weakening of the implementation of moral values ​​and the emergence of various social problems such as drug abuse, online gambling, brawls, promiscuity, and low religious participation. This study aims to determine the implementation of moral values ​​in the social interactions of Generation Z, analyze supporting factors, and identify barriers to their implementation. This study used a descriptive qualitative approach with a phenomenological field research design. Primary data were obtained through in-depth interviews and participant observation with religious leaders, community leaders, parents, and Generation Z youth, while secondary data were sourced from Islamic moral literature and previous research. The results indicate that the implementation of moral values ​​is ambivalent across four dimensions: morality towards God, fellow human beings, nature, and oneself, with the most prominent violations occurring in the morality dimension toward oneself. Supporting factors include family role models and local religious culture, while major obstacles include the influence of social media, weakened social control due to fishermen’s irregular working hours, and peer pressure. The novelty of this research lies in the formulation and implementation of four community-based moral development programs for coastal fishermen, which have not been widely studied in previous literature. This study recommends strengthening social bonds based on religious values ​​as a more effective strategy for fostering the morals of Generation Z than repressive approaches.